The integrated disease management of early blight in organically grown tomato under hill condition of Sikkim, India - Shivakoty, Pravesh; Basu, Amitava; Maji, Pijush Kanti; Thapa, Sukhram (Asia Pacific Journal of Sustainable Agriculture, Food and Energy, 2023)
Tomato (Lycopersicon esculentum Mill.) is the most widely cultivated vegetable crop in the world and early blight caused by Alternaria spp. is one of the major production constraints. Survey was conducted during kharif seasons of 2018-19 &2019-20 in four districts of Sikkim. Maximum early blight disease severity was recorded in south district of Sikkim. Pathogenicity test of isolates collected from different location were established. Morphological, cultural, and molecular identification of the pathogen reveal pathogen as Alternaria spp. Five different bio-control agents i.e., Trichoderma harzianum, T. Viride, Pseudomonas fluorescens, Bacillus subtilis and Bacillus cereus were evaluated against the test pathogens. Among the bio-control agents tested, Trichoderma harzianum (74.89%) and Trichoderma viride (69.41%) showed maximum percent growth inhibition. Open field experiment was conducted with eleven treatments formulated by integrating the different organic inputs, biocontrol agents and copper-based fungicide as chemical check. Organic treatment T9 {Susceptible Variety + Soil treatment with Trichoderma harzianum @1:25(1kg Trichoderma + 25 Kg of FYM) + cow dung slurry 10% + Nimbicidine 0.3% + Panchagavya 10% + Cow Urine 10%} consistently showed the best result among the bioresources tested. Keywords: Tomato, Organic, Bio agent and Integrated disease management